A new approach for reducing pollutants level: a longitudinal cohort study of physical exercises in young people - Yujuan Xu; Hongliang Gao; Zhixiang Du; He Liu; Qi Cheng; Furong Zhang; Juan Ye; Aiqing Wang; Yanjun Dou; Bei Ma; Ningwei Zhao; Feng Zhu; et al. (BMC, 2022)
Abstract Background The present study aimed to evaluate the elimination of three common pollutants (dimethoate, benzo(a)pyrene (BaP) and bisphenol A (BPA) by different physical exercises and to assess the possible factors which could affect the pollutants elimination. Methods A total of 200 individuals who chose different kinds of exercises in accordance to their own wish were recruited. The levels of urinary pollutants were measured using β-glucuronidase hydrolysis followed by a high-performance liquid chromatography tandem mass spectrometry-based method. Results Totally, the levels of dimethoate, BaP and BPA were reduced after physical exercises. However, the elimination of BaP in male was higher than that in female but the elimination of BPA in female was higher than that in male. Multivariate logistic regression showed that the degree of heart rate (HR) change was a protective factor affecting the improvement effect of dimethoate, BaP and BPA while BMI (body mass index) was a risk factor. Nevertheless, sex was a risk factor affecting the improvement of dimethoate and BaP but had a lower efficacy on BPA improvement. Conclusion The present findings indicate that physical exercises can be considered as a novel approach to eliminate pollutants level in human body and can also give suggestions for choosing specific physical exercises to male and female individuals. Moreover, those who are with higher BMI need to lose weight before eliminating pollutant level through physical exercises.